The level of English achieved in fifth grade of secondary school at three public schools in metropolitan Lima - García Ponce, Isabel (2019)
This research is framed in the context of the Peruvian public education, where the teaching of the English language has been the objective of unsuccessful reforms aimed at improving the situation of oblivion in which it has been for decades. At a time when the Ministry of Education has launched a new policy to ensure that all students who graduate from public school can express their ideas efficiently in English, it is advisable to know the effectiveness of these changes. Using data collected from the protagonists, this study gives account of the factors that are facilitating or impeding its implementation, as well as their early successes, to identify useful elements for decisions that ensure the quality of the teaching of English in public schools.